Area deprivation and the food environment over time: A repeated cross-sectional study on takeaway outlet density and supermarket presence in Norfolk, UK, 1990–2008. (May 2015) - Maguire, Eva R.; Burgoine, Thomas; Monsivais, Pablo
Abstract: Socioeconomic disparities in the food environment are known to exist but with little understanding of change over time. This study investigated the density of takeaway food outlets and presence of supermarkets in Norfolk, UK between 1990 and 2008. Data on food retail outlet locations were collected from telephone directories and aggregated within electoral wards. Supermarket presence was not associated with area deprivation over time. Takeaway food outlet density increased overall, and was significantly higher in more deprived areas at all time points; furthermore, socioeconomic disparities in takeaway food outlet density increased across the study period. These findings add to existing evidence and help assess the need for environmental interventions to reduce disparities in the prevalence of unhealthy food outlets. Highlights: We examined disparities in the retail food environment over 18 years in Norfolk, UK Supermarket presence was not associated with area-level deprivation Takeaway food outlet density was significantly greater in more deprived areas Socioeconomic inequalities in takeaway food outlet density increased over time